2022
DOI: 10.1007/s00203-022-03295-w
|View full text |Cite
|
Sign up to set email alerts
|

Valorization of Parmentiera aculeata juice in growth of probiotics in submerged culture and their postbiotic production: a first approach to healthy foods

Abstract: Actually, functional foods are good accepted for consumers for to improves health and new sources of substrates are explored. However, Parmentiera aculeate, which is a plant distributed in Mexico, has not explored. The P. aculeata juice was used as unique carbon source of promote the growth of two probiotic strains in Submerged Fermentation. Taguchi methodology with orthogonal array L9 was applied for its optimization. pH, agitation and inoculum concentration with three levels were evaluated and the best treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Some works have already reported using by-products as substrates for postbiotic production, such as cheese whey, milk permeate, and lignocellulosic biomass [8,9]. Recently, it was demonstrated that the juice from Parmentiera aculeata, a plant that is available in Mexico, increased synthesis of postbiotics like succinic acid, formic, acetic, propionic, and lactic acids as well as development of Lactobacillus plantarum [10].…”
Section: Introductionmentioning
confidence: 99%
“…Some works have already reported using by-products as substrates for postbiotic production, such as cheese whey, milk permeate, and lignocellulosic biomass [8,9]. Recently, it was demonstrated that the juice from Parmentiera aculeata, a plant that is available in Mexico, increased synthesis of postbiotics like succinic acid, formic, acetic, propionic, and lactic acids as well as development of Lactobacillus plantarum [10].…”
Section: Introductionmentioning
confidence: 99%